Copper oxide/polyaniline nanocomposites-blended in palm oil hybrid nanofluid: Thermophysical behavior evaluation - Sofiah, A. G. N.; Mahendran, Samykano; Sudhakar, K.; Said, Zafar; Pandey, A. K. (Elsevier, 2023)
In the present work, Copper Oxide-Polyaniline (CuO/PANI) nanocomposites-blended in palm oil hybrid nanofluid have been prepared via a two-step method and investigated as potential heat transfer hybrid nanofluids for the first time. Initially, CuO/PANI nanocomposites are synthesized via oxidative polymerization by varying the weight percentage of CuO nanoparticles (1, 5, and 10 wt%) and characterized using TEM, EDX, XRD, FTIR, and TGA analysis. The findings revealed a successful fusion of nanocomposite composed of spherical CuO nanoparticles embedded in flake-like PANI. The formulated CuO/PANI-palm oil hybrid nanofluids are prepared at a volume concentration between 0.01% and 0.5% and stabilized using an ultrasonication process without any surfactant. UV–vis and sedimentation observation revealed that all nanofluids remain stable for up to a month. FTIR analysis reveals that all formulated nanofluids are chemically stable as no formation of new peaks obtained with the dispersion of nano additives. The TGA analysis affirmed better thermal stability in all nanofluids compared to base fluids. Density evaluation of formulated nanofluids shows a linear relationship between density and volume concentration of nanocomposites but decreased with temperature. Rheology study indicates that palm oil exhibits viscous flow behavior similar to Newtonian behavior. Nanofluid containing 10 wt% CuO/PANI nanocomposites displayed having the highest viscosity and thermal conductivity properties (31.34% enhancement) compared to the rest prepared nanofluids. Mathematical equations were developed at the final stage of the research for future properties prediction.